Synergistic Antimicrobial Interaction between Honey and Phage against Escherichia coli Biofilms - Oliveira, Ana; Ribeiro, Henrique G.; Silva, Ana C.; Silva, Maria D.; Sousa, Jessica C.; Rodrigues, Célia F.; Melo, Luís D. R.; Henriques, Ana F.; Sillankorva, Sanna (Frontiers in Microbiology, 2017)
Chronic wounds afford a hostile environment of damaged tissues that allow bacterial proliferation and further wound colonization. Escherichia coli is among the most common colonizers of infected wounds and it is a prolific biofilm former. Living in biofilm communities, cells are protected, become more difficult to control and eradicate, and less susceptible to antibiotic therapy. This work presents insights into the proceedings triggering E. coli biofilm control with phage, honey and their combination, achieved through standard antimicrobial activity assays, zeta potential and flow cytometry studies and further visual insights sought by SEM and TEM microscopy. Two Portuguese honeys (PF2 and U3) with different floral origin and an E. coli specific phage (EC3a), possessing depolymerase activity, were tested against 24 h and 48 h-old biofilms. Synergic and additive effects were perceived in some phage-honey experiments. Combined therapy prompted similar phenomena in biofilm cells, visualized by electron microscopy, as the individual treatments. Honey caused minor membrane perturbations to complete collapse and consequent discharge of cytoplasmic content, and phage completely destroyed cells leaving only vesicle-like structures and debris. Our experiments show that the addition of phage to low honey concentrations is advantageous, and that even 4-fold diluted honey combined with phage, presents no loss of antibacterial activity towards E. coli. Portuguese honeys possess excellent antibiofilm activity and may be potential alternative therapeutic agents in biofilm-related wound infection. Furthermore, to our knowledge this is the first study that assessed the impacts of phage-honey combinations in bacterial cells. The synergistic effect obtained was shown to be promising, since the antiviral effect of honey limits the emergence of phage resistant phenotypes.